Assessment of the Clinical Trials Safety Profile of PD-1/PD-L1 Inhibitors Among Patients With Cancer: An Updated Systematic Review and Meta-Analysis - Tian, Yuan; Huang, Alan; Yang, Yue; Dang, Qi; Wen, Qing; Wang, Linlin; Sun, Yuping (Frontiers in Oncology, 2021)
Background Understanding the safety and adverse event profiles of PD-1/PD-L1 inhibitors is important in guiding cancer immunotherapy. Consequently, we designed this meta-analysis to evaluate the safety of PD-1/PD-L1 inhibitors in clinical trials involving cancer patients. Methods Four safety indicators comprising treatment-related adverse events, death, discontinuation of therapy and grades 3–5 adverse events were evaluated using the random effect model. The quality of enrolled trials was assessed using the Newcastle Ottawa Scale (NOS). Results Forty-four clinical trials were included in the final meta-analysis. Compared with chemotherapy, the risk of death due to the use of PD-1/PD-L1 inhibitors was much lower than that experienced in the control group (OR = 0.65, 95%CI: [0.47, 0.91], I2 = 0%, Z = 2.52 (P = 0.01)). Similar observations were apparent regarding the other three indicators of safety and also when the use of PD-1/PD-L1 inhibitors alone is compared with the combined use of PD-1/PD-L1 and CTLA-4. When used together with chemotherapy, PD-1/PD-L1 inhibitors increased the incidence of the adverse events as compared to the use of chemotherapy alone. Increased risks for adverse events were also noticed with the use of PD-1/PD-L1 inhibitors over the use of a placebo. Conclusion The use of PD-1/PD-L1 inhibitors alone is associated with a better safety profile compared to either the use of chemotherapy or the use of PD-1/PD-L1 inhibitors with other anticancer regimens.